EKONOMI ISLAM DALAM KONTEKS KE-INDONESIA-AN ( PERSPEKTIF JALAN KETIGA ) - Ery Wibowo Agung Santoso (Universitas Muhammadiyah Semarang, 2011)
This paper is a literature study to trace the influence of Islamic values ​​in economic practice in Indonesia. Koperasi concepts can be said as a metamorphosis of Islamic economics in the context of Indonesia's. Establishment of primary cooperatives based real sector of agriculture and trade is a form of defense mechanism to combat usury as gharar or speculation, harmfull monopoly and other forms of usury. The concept and the idea is actually equal to the concepts and ideas of Islamic economics. In theory the concept of hegemony can be categorized as The Third Way or